Pengaruh Kompetensi Sumber Daya Manusia, Sistem Pengendalian Internal dan Pengalaman terhadap Efektivitas Pengelolaan Dana Kelurahan - Tamsil Tamsil; Yusriadi Hala; Rostiaty Yunus; Arsyad Paweroy (Al-Buhuts, 2026)
The effectiveness of urban village fund management is greatly influenced by the capacity of government officials and management mechanisms that can ensure the effective and accountable use of funds. In this context, human resource competence, internal control systems, and the experience of government officials are important aspects that must be considered. This study aims to analyze the influence of human resource competence, internal control systems, and civil servant experience on the effectiveness of village fund management in Tamalate District, Makassar City. The study employed a quantitative approach using a saturation sampling technique targeting village fund managers. Data were collected via questionnaires and analyzed using multiple linear regression. The results indicate that human resource competence has a positive and significant effect on the effectiveness of village fund management, with a regression coefficient of 0.3441 and a p-value of 0.0000. The internal control system had a positive and significant effect with a coefficient of 0.2200 and a p-value of 0.0001, while the experience of civil servants had a positive and significant effect with a coefficient of 0.1600 and a p-value of 0.0015. Human resource competence demonstrated the relatively greatest influence compared to the other variables. These findings imply that local governments need to prioritize improving civil servant competence, along with strengthening internal control systems and developing work experience, to enhance the effectiveness of village fund management. This study contributes by demonstrating that aspects of civil servant capacity and internal governance are empirically important factors in supporting the effectiveness of village fund management at the local level.